2021
DOI: 10.1002/pds.5230
|View full text |Cite
|
Sign up to set email alerts
|

Identifying prescribing cascades in Alzheimer's disease and related dementias: The calcium channel blocker‐diuretic prescribing cascade

Abstract: Purpose: Prescribing cascades occur when a physician prescribes a new drug to address the side-effect of another drug. Persons with Alzheimer's disease and related dementias (ADRD) are at increased risk for prescribing cascades. Our objective was to develop an approach to estimating the proportion of calcium channel blockerdiuretic (CCB-diuretic) prescribing cascades among persons with ADRD in two U.S. health plans. Methods:We identified patients aged ≥50 on January 1, 2017, dispensed a drug to treat ADRD in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 13 publications
1
19
0
1
Order By: Relevance
“…These results also reaffirm the necessity of using a control group either by incorporating pre‐index prescribing of a marker drug (i.e., a PSSA) 10 or using of alternative medication not associated with the outcome using a cohort design 21 as a lack of a control group could result in an overestimation of attributing the marker drug to a prescribing cascade 22 …”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…These results also reaffirm the necessity of using a control group either by incorporating pre‐index prescribing of a marker drug (i.e., a PSSA) 10 or using of alternative medication not associated with the outcome using a cohort design 21 as a lack of a control group could result in an overestimation of attributing the marker drug to a prescribing cascade 22 …”
Section: Discussionsupporting
confidence: 58%
“…20 These results also reaffirm the necessity of using a control group either by incorporating pre-index prescribing of a marker drug (i.e., a PSSA) 10 or using of alternative medication not associated with the outcome using a cohort design 21 result in an overestimation of attributing the marker drug to a prescribing cascade. 22 There are a few limitations to note. First, findings of the prescribing cascade validation may not be generalizable to other health systems or other prescribing cascades, thus, while we demonstrate proof of concept of the symmetry assumption, explicit testing using similar methods as described here should be conducted for other PSSAs.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies ( n = 88) were retrospective cohort studies, 5 , 7 , 18 , 21 , 23 , 24 , 25 , 26 , 27 , 29 , 30 , 31 , 32 , 33 , 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , …”
Section: Resultsunclassified
“…In one study examining the CCB-loop diuretic prescribing cascade, an additional medical chart review was also conducted. 107 The suspected ADRs, symptoms or new diagnoses explored were broad-ranging (see Table 2) most commonly depression (n=13) 33,37,40,45,52,55,57,73,95,99,100,112,114 ; peripheral oedema (n=11) [5][6][7]28,36,64,81,98,[105][106][107]118 ; urinary incontinence (n=9). 24,26,41,44,50,53,75,81,119 and parkinsonism (n=9) 27,29,31,46,57,81,84,123,124…”
Section: Suspected Adverse Reaction(s)mentioning
confidence: 99%
“…91,93,103 No association between drug pairs could be determined for several studies, largely due to either a crosssectional study design examining concurrent drug use, insufficient drug-pair sample size to determine a sequence ratio or reporting of incidence rates with no incidence rate ratio (labelled N/A in Figure 2). 6,21,25,43,46,53,55,64,81,114,116,117,123,125,126 Several studies reported at least one negative association between drug pairs, indicating a reduced likelihood of the second medication being initiated (see eTable 3 Supplementary materials). 33,60,[68][69][70]75,83,89,91,95,113 Modifiers of identified associations Older people (aged [?…”
Section: New Medication(s) Prescribedmentioning
confidence: 99%